Manual de procesos para la empresa COELEC S. C. del cantón de Santo Domingo, provincia de Santo Domingo de los Tsáchilas, año 2014 - Mocha Crespo, Edison Fernando (2015)
The thesis aims to propose new and better processes in the different areas that make up the company Coelec SC., for the flow of economic activity therein, optimally to re-position the company as the best of the canton Santo Domingo de los Colorados, for which it has been developed present manual of process. In order to meet the goals outlined in this investigation methods were used: inductive, deductive, analytical and deductive, the types of research applied are bibliographic, descriptive was field done specifically in the site, was used investigation techniques to collect information, was employed the formula of population and sample results were 217 customers surveyed and 34 partners representing 100%. For other part, the tabulating survey shows us that 93% are regular customers, 55% do not receive good care, and 70% disagreed with the current processes, the 98% of companies that need electrical material agrees with products marketed, the 93% of customers says he would not return to buy in the company Coelec SC, If the company does not change the processes. In order that does not exist is no loss of customers the company, must be implemented the manual of processes proposed here, where employees must improve their fitness to clients and colleagues, plus other proposed indications here, this will increase the sales and will improve the time response in to the delivery of the products, for which ratify be the largest and most comprehensive provider of electrical supplies in the region.